Top Managers and Information Systems: 'Crossing the Rubicon!'1. (May 2014) - Loonam, John; McDonagh, Joe; Kumar, Vikas; O'Regan, Nicholas
<x xml:space="preserve">Abstract</x> Supporting information systems requires both thought and action, which managers should consider in a consistent roadmap before 'crossing the Rubicon' to adopt such systems.